The uses of Internet and the social media by the Portuguese teachers’ unions - Marques Alves, P. (IV International Meeting of Industrial Sociology, Sociology of Organisations and Work (ISSOW). Work (In)equalities and Social Relations in the Digital Economy, 2021)
The trade union movements are facing a profound crisis since the 70s. The causes are multiple, including factors that are exogenous to them and others that are endogenous, referring to its bureaucratization and oligarchization. Aiming to revitalize, they have been implementing several actions, among which the adoption of the Internet. In this paper we intend to analyze the adoption of the Internet by the Portuguese teachers’ unions and how they are using it, both in terms of websites and social media, trying to understand if this use is allowing or not the deepening of organizational democracy, a crucial factor for the union’s revitalization. With that purpose, we analyzed the official websites of the unions and their presence in the social media, mainly in Facebook, Twitter and You Tube. In a context of a huge fragmentation of the teacher’s union movement, our findings show that the Internet and the social media are being used intensively, but with different purposes. For instance, some unions used them mainly for mobilizing; others basically for information. However, there is a convergence in the fact that the use that it is made is not creating the conditions for the enhancement of the participation of the membership and the deepening of the accountability. A relative exception is STOP, a newly founded union. In this case, it takes advantage of the potential of the new media through the promotion of participation, for instance, by answering the questions or comments that are posted in Facebook. So, we will conclude by stating that, given the static nature and the little interactivity that characterize the official websites of these unions and how the other platforms are used, the unions are losing an opportunity to contribute to the deepening of the democratic forms of associative government and therefore to strengthen trade unionism. Moreover, in the context of the protest against the devaluation of the profession it is clear that the use that it is made in this particular do not allow us to state that unions have fundamentally changed the way they act in the Internet.